Incident retinal vein occlusions and estimated cerebrospinal fluid pressure: the Beijing Eye Study - Jonas, Jost B. (Acta ophthalmologica, 2015)
Purpose To examine whether the incidence of retinal vein occlusions (RVOs) is associated with estimated cerebrospinal fluid pressure (CSFP). Methods The population-based Beijing Eye Study, which included 4439 subjects (age: 40 + years) in 2001, was repeated in 2011 with 2695 subjects participating (66.4% of the survivors). Fundus photographs were examined for the new development of RVOs, differentiated into central RVOs (CRVOs) and branch RVOs (BRVOs). CSFP was calculated as CSFP [mmHg] = 0.44 × Body Mass Index [kg/m2] + 0.16 × Diastolic Blood Pressure [mmHg]−0.18 × Age[Years]. Results Incident BRVOs were detected in 50 eyes and incident CRVOs in 8 eyes. BRVOs were located at arterio-venous crossings in 39 eyes. In multivariate analysis, a higher estimated CSFP was associated with a higher incidence of CRVOs (p = 0.004; standardized coefficient beta: 0.06; regression coefficient B: 5.35; 95% confidence interval (CI):1.73, 8.96) after adjusting for urban region (p < 0.001; beta: −0.52; B: −3.93; 95% CI: −4.29, −3.57), higher educational level (p = 0.001; beta: 0.13; B: 0.44; 95% CI: 0.28, 0.60), higher blood concentrations of triglycerides (p < 0.001; beta: 0.08; B: 0.11; 95% CI: 0.05, 0.16) and higher intraocular pressure (p < 0.001; beta: 0.16; B:0.21; 95% CI: 0.16, 0.27). As a corollary, a higher incidence of RVOs as a whole, as well as a higher incidence of CRVOs combined with a higher incidence of BRVOs originating at the optic nerve head, both were significantly associated with higher estimated CSFP (p = 0.002; odds ratio (OR): 1.15; 95% CI: 1.05, 1.25; and p = 0.037; OR: 1.17; 95% CI: 1.01, 1.35, respectively) after adjusting for older age. Conclusions A higher estimated CSFP was associated with a higher incidence of RVOs originating at the optic nerve head (i.e. CRVOs, hemi-central RVOs and BRVOs originating at the optic nerve head), and vice versa, a higher incidence of RVOs was associated with a higher estimated CSFP. It suggested an influence of higher estimated CSFP on higher central retinal vein pressure.